Dual-band implantable antennas for medical telemetry: A fast design methodology and validation for intra-cranial pressure monitoring - Kiourti, A.; K. A. Psathas; Costa, J. R.; C. A. Fernandes; Nikita, K. (Progress in Electromagnetics Research, 2013)
In this study, we suggest and experimentally validate a methodology for fast and optimized design of dual-band implantable antennas for medical telemetry (MICS, 402-405 MHz, and ISM, 2400-2480 MHz). The methodology aims to adjust the design of a parametric dual-band antenna model towards optimally satisfying the requirements imposed by the antenna-fabrication procedure and medical application in hand. Design is performed in a systematic, fast, and accurate way. To demonstrate its effectiveness, the proposed methodology is applied to optimize the parametric antenna model for intra-cranial pressure (ICP) monitoring given a specific antenna-fabrication procedure. For validation purposes, a prototype of the optimized antenna is fabricated and experimentally tested. The proposed antenna is further evaluated within a 13-tissue anatomical head model in terms of resonance, radiation, and safety performance for ICP monitoring. Extensive parametric studies of the optimized antenna are, finally, performed. Feasibility of the proposed parametric antenna model to be optimally re-adjusted for various scenarios is demonstrated, and generic guidelines are provided for implantable antenna design. Dual-band operation is targeted to ensure energy autonomy for the implant. Finite Element (FE) and Finite Difference Time Domain (FDTD) simulations are carried out in homogeneous rectangular and anatomical head tissue models, respectively.